Variability of Eu2+ Emission Features in Multicomponent Alkali-Metal-Rare-Earth Sulfides. (1st January 2020) - Jarý, V.; Havlák, L.; Bárta, J.; Buryi, M.; Rejman, M.; Pokorný, M.; Dujardin, Ch.; Ledoux, G.; Nikl, M.
Abstract : A set of multicomponent sulfide-based phosphors of general formula ARES2 : 0.05% Eu, where A represents any combination of Rb, K, Na and RE is any combination of La, Gd, Lu and Y, was synthesized in the form of transparent hexagonal crystalline platelets by inorganic reaction under the flow of H2 S gas. X-ray diffraction and X-ray fluorescence were employed to investigate their structural properties and intrinsic chemical composition. Optical properties connected to the Eu 2+ emission center present in these sulfidic hosts, including photoluminescence excitation and emission spectra as well as the overall emission spectra of circadian light source, were measured by means of luminescence spectroscopy using either PMT or CCD as detection elements. Electron paramagnetic resonance (EPR) was utilized in order to understand the mechanism of the Eu 2+ ions incorporation into the ARES2 structure. Important parameters connected to phosphors to be used in solid state white LED technology, such as x, y coordinates in the CIE color space, color correlated temperature (CCT), color rendering index (CRI) and color quality scale (CQS) were calculated from the experimentally obtained emission spectra. Application potential of given phosphors in solid state lighting technology was discussed thoroughly.